Subjectivity of Women in Oka Rusmini’s Novel Tempurung (2010): Self in Marriage, Pregnancy and Mothering - Anita Dhewy (Jurnal Perempuan, 2015)
This paper aims to explain female subjectivity reflected in Tempurung novel by Oka Rusmini by describing main character perception toward body and autonomy in the formation of female subjectivity. In discussion I use feminist literary criticism approach. This study reveals that woman characters in Tempurung perceiving her body as a significant part of her subjectivity. Furthermore, female subjectivity isn’t her own project but a form of dialogue with other elements including her relationship with husband, children, body and social culture construction which surrounding her. The conclusion of this study is Oka Rusmini makes resistance to the notion of subjectivity on conventional/ traditional thought by representing narrative of female subjectivity which doesn’t neglect body, doesn’t individual, doesn’t always rational, doesn’t subject to “universal” notion of subject and doesn’t finish.